MERGER INVESTIGATION OF BANK MANDIRI SYARIAH AS AN EFFORT TO STRENGTHEN THE SHARIA ECONOMIC ECOSYSTEM - Mohamed, Hussein; Darussalam, Darussalam (Journal Of Islamic Ekonomic and Business, 2023)
Abstract This study discusses the Merger Analysis of PT Bank Mandiri Syariah to Become Bank BSI as an Effort to Strengthen the Islamic Economic Ecosystem. The Merger of Bank Syariah Indonesia that was carried out was a merger of the three large Islamic Banks in Indonesia, namely Bank Mandiri Syariah, Bank BRI Syariah, and Bank BNI Syariah. This research will focus more on discussing the impact that will occur on the Islamic economy in Indonesia from the merger of these three banks. And what are the strategies in an effort to improve the Islamic Economic Ecosystem. This research also aims to further introduce the achievements of the merger of Bank Syariah Indonesia and at the same time provide further insight and knowledge to the public and also especially students of the Islamic Banking study program in using the right tools for transactions. The method used by the author in this study is to use a quantitative calculation approach that has been obtained from data collection by the author. The author performs calculations on the growth of Assets, Liabilities, Equity, Mudharabah, and Musyarakah at PT. Bank Mandiri Syariah. With the results of research that the growth of Assets, Liabilities, Equity, Mudharabah, and Musyarakah that occurred over the last five years shows a very volatile growth rate. And the impact on the merger of Bank Syariah Indonesia is also in line with the results of this growth, where financial performance has been very positive and this is also what is expected to help increase in strengthening the Islamic Economic Ecosystem in Indonesia.